PENGARUH PENDEKATAN MATEMATIKA REALISTIK BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK KELAS VII - Aulia Anggun Mutiara; Izwita Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of students’ mathematical critical thinking skills at SMP Negeri 3 Satap Teluk Mengkudu remains a challenge in the mathematics learning process. This study aims to investigate the effect of the realistic mathematics education approach based on ethnomathematics on the critical thinking skills of seventh-grade students. The research was conducted in the first semester of the 2025/2026 academic year using a one-group pretest-posttest design. The sample was selected through purposive sampling, with class VII-1 designated as the experimental group. Descriptive analysis results indicate an increase in the mean score from 48.05 in the pretest to 78.71 in the posttest. The paired sample t-test produced a significance value of 0.000 (<0.05), indicating a significant difference between the pretest and posttest results. Furthermore, the effect size calculation of 3.68 demonstrates a very large impact. Thus, it can be concluded that the realistic mathematics education approach based on ethnomathematics is effective in enhancing students’ mathematical critical thinking skills. Future studies are recommended to expand the scope and explore other aspects, such as conceptual understanding, problem-solving ability, and creative thinking.